Designing Marketing Strategy Based on Value from Clothing-producing Companies using the AHP and Delphi Methods - Hasrini Sari; Diningtyas Aulia Nurhadi (Department Industrial Engineering, University of Muhammadiyah Malang, 2019)
Organizations design some strategies to win the competition. This paper discusses the design of market strategies to achieve harmony between value-based segmentation and marketing mix. The strategy's implementation starts with segmentation, targeting, and positioning. The clothing company (